HUBUNGAN PERILAKU DAN PERSONAL HYGIENE IBU DENGAN KEJADIAN KECACINGAN PADA BALITA DI WILAYAH KERJA PUSKESMAS GALANG TAHUN 2019 - Fithri Handayani Lubis; Tria Puspita Dewi Ginting; Rawelven Purba (JURNAL KESMAS DAN GIZI (JKG), 2020)
Health behavior is all activities of a person that can be observed or which cannot be observed that are related for health care and improvement. Helminthiasis is the infectious of disease whose prevalence is very high in Indonesia, especially intestinal worms that are transmitted through soil (Soil Transmitted Helminth ).Worm disease is widespread in both rural and urban areas. The problem of this research there is relationship between behavior and personal hygiene of the mother with helminthiasis incident in infants in the work area of Galang Public Health Center in 2019. the type of research used is using survey research that is analytical survey with a cross sectional survey approach to learn the correlation dynamics between risk factors by effects, by approach, observation data colletion in the same time (point time approach). Population of the research 160 mothers the sample of this research is 62 mothers that have baby in Galang Public Health Center . the variable of the researched to knowing about relationship behavior and personal hygiene of the mother with helminthiasis incident as independent variable and helminthiasis in infant as dependent variable .the Data is by questionnaire technique. The Data obtained were analyzed using univariate and bivariate analysis. The result of the research showed that based on personal hygiene mothers who behaved adequately as many as 39 peoples (62,9%) while the mothers who behaved had good hygiene was 23 people (37,1). The result showed that helminthiasis incident in infants as many as 39 peoples ( 62.9%) research while those who did not develop helminthiasis in infants were 23 peoples (37.1%). The result of chisquare test a many as.. with p value 0.007(p<0.05) that means Ho is rejected and Ha accepted. There in significant relationship between behavior and personal hygiene of the mother with helminthiasis incident in infanst in the work area of Galang Public Health Center in 2019.